2011
DOI: 10.1007/s00198-011-1728-5
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 promotes both osteoblastogenesis and novel osteoclastogenic signals in ST2 mesenchymal progenitor cells

Abstract: Summary We profiled the global gene expression of a bone marrow-derived mesenchymal pluripotent cell line in response to Runx2 expression. Besides osteoblast differentiation, Runx2 promoted the osteoclastogenesis of co-cultured splenocytes. This was attributable to the upregulation of many novel osteoclastogenic genes and the downregulation of anti-osteoclastogenic genes. Introduction In addition to being a master regulator for osteoblast differentiation, Runx2 controls osteoblast-driven osteoclastogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 123 publications
(137 reference statements)
6
52
0
3
Order By: Relevance
“…In the present study, we discovered that the expression of Runx2 was decreased post-MP treatment, whereas it was upregulated after the transplantation of SDF-1α-GFP-BMSCs, which is consistent with the results of previous studies [52, 53]. Lingqian et al reported that the cotherapy with the parathyroid hormone (PTH) and SDF-1 promoted osteogenic differentiation of human periodontal ligament stem cells by enhancing OCN expression and ALP activity [54], which is in line with the findings of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we discovered that the expression of Runx2 was decreased post-MP treatment, whereas it was upregulated after the transplantation of SDF-1α-GFP-BMSCs, which is consistent with the results of previous studies [52, 53]. Lingqian et al reported that the cotherapy with the parathyroid hormone (PTH) and SDF-1 promoted osteogenic differentiation of human periodontal ligament stem cells by enhancing OCN expression and ALP activity [54], which is in line with the findings of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Sema 7A was the most up-regulated gene among semaphorin family members in hDFCs (Table 1). Previous reports have also confirmed the expression of Sema 7A mRNA in mouse osteoblast cell lines and in primary calvarial osteoblasts 17,26) . We confirmed the gene expression of Sema 7A in hDFCs using RT-PCR and real-time PCR.…”
Section: Expression Of Semaphorin 7a Receptors During Osteogenic Diffsupporting
confidence: 59%
“…Expression of Sema 7A was low at the start of osteoclast culture from spleen-derived cells, and was high during immature osteoclast fusion 17,26) . Sema7A increases cell fusion, as exposure to exogenous Sema 7A during differentiation enhanced the number of nuclei per osteoclast and reduced the number of individual osteoclasts 17) .…”
Section: Expression Of Semaphorin 7a Receptors During Osteogenic Diffmentioning
confidence: 99%
“…Additionally, previous study demonstrated that 12 putative Cbfa1/Runx2-binding elements (osteoblast-specific element 2-OSE 2 ) were presented in human OPG promoter sequence and Runx2 could bind to the proximal OSE 2 to increase OPG expression level [36]. Further, when doxycycline was used to induce increased expression of Runx2 in ST2 cells (a bone marrow-derived mesenchymal pluripotent cell line), the differentiation of cocultured splenocytes into osteoclasts was enhanced along with the inhibition of OPG [37], which result was consistent with our data. Thus, it can be supposed that Runx2 may directly regulate the expression of OPG in PDLSCs.…”
Section: Figmentioning
confidence: 99%